Forms And Types of Physical Culture, Sports Activities in Educational Institutions - Sh.Q. Alimov (Genius Journals, 2021)
Physical education plays an important role in educating the younger generation as healthy and well-rounded people. The main goal of physical education is rehabilitation, and physical education activities have a healing effect. Exercise and physical movement, along with the formation of movement skills and abilities, improve physical qualities. In general, it carries out the physical development of the organism with the increase of biological functions and body weight, height growth, improvement of the musculoskeletal system
Keywords: Technique; movement; strength; agility